2023
DOI: 10.1038/s41598-023-31769-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human oxidoreductases involved in aldehyde odorant metabolism

Abstract: Oxidoreductases are major enzymes of xenobiotic metabolism. Consequently, they are essential in the chemoprotection of the human body. Many xenobiotic metabolism enzymes have been shown to be involved in chemosensory tissue protection. Among them, some were additionally shown to be involved in chemosensory perception, acting in signal termination as well as in the generation of metabolites that change the activation pattern of chemosensory receptors. Oxidoreductases, especially aldehyde dehydrogenases and aldo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 68 publications
4
13
0
Order By: Relevance
“…While some proteomic analyses did not detect DCXR, 40 others were sensitive enough to verify the protein in the human nasal mucus. 14 DCXR protein has been previously found in the human respiratory mucosa, 5 which is in line with what we observed in the present study. According to the human protein atlas, 41 DCXR has also been detected in low amounts in fibroblasts, which could explain the punctual staining observed in the fibroblast-loaded connective tissue.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…While some proteomic analyses did not detect DCXR, 40 others were sensitive enough to verify the protein in the human nasal mucus. 14 DCXR protein has been previously found in the human respiratory mucosa, 5 which is in line with what we observed in the present study. According to the human protein atlas, 41 DCXR has also been detected in low amounts in fibroblasts, which could explain the punctual staining observed in the fibroblast-loaded connective tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning ALDH1A1, its expression in the human nasal turbinate and olfactory cleft has been previously shown by our team. 14 We demonstrated that this enzyme is strongly expressed in the epithelial layer. As ADLH1A1 is a secreted enzyme, we suggested that nasal glands might be involved in this process.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Human aldehyde dehydrogenases have recently been discovered to metabolize odorant aldehydes. Additionally, in the same study, these enzymes were shown to be highly expressed in the oral cavity (Boichot et al., 2023).…”
Section: The Role Of the Oral Microbiota In Aroma Release And Perceptionmentioning
confidence: 82%